Derivada

π‘»π’†π’π’“π’†π’Žπ’‚. βˆ’π‘†π‘– πΏβˆ’1 {𝑓(𝑠)} = 𝐹(𝑑) π‘’π‘›π‘‘π‘œπ‘›π‘π‘’π‘  πΏβˆ’1 {𝑓 (𝑛) (𝑠)} = (βˆ’1)𝑛 𝑑 𝑛 𝐹(𝑑)

π‘«π’†π’Žπ’π’”π’•π’“π’‚π’„π’Šπ’π’
𝑑𝑛
π‘π‘œπ‘šπ‘œ 𝐿{𝑑 𝑛 𝐹(𝑑)} = (βˆ’1)𝑛 𝐿{𝐹(𝑑)} = (βˆ’1)𝑛 𝑓 (𝑛) (𝑠)
𝑑𝑠 𝑛

π‘‘π‘œπ‘šπ‘Žπ‘›π‘‘π‘œ π‘™π‘Ž π‘–π‘›π‘£π‘’π‘Ÿπ‘ π‘Ž π‘Ž π‘Žπ‘šπ‘π‘œπ‘  π‘šπ‘–π‘’π‘šπ‘π‘Ÿπ‘œπ‘  π‘³βˆ’πŸ {𝒇(𝒏) (𝒔)} = (βˆ’πŸ)𝒏 𝒕𝒏 𝑭(𝒕)

EJEMPLO
𝒔+𝟐
𝑯𝒂𝒍𝒍𝒂𝒓 π‘³βˆ’πŸ {𝒍𝒏 ( )}
𝒔+𝟏
π‘π‘œπ‘šπ‘œ 𝐿{𝑑𝐹(𝑑)} = βˆ’π‘“ β€² (𝑠) οƒž πΏβˆ’1 {𝑓 β€² (𝑠)} = βˆ’π‘‘πΉ(𝑑) οƒž πΏβˆ’1 {𝑓 β€² (𝑠)} = βˆ’π‘‘πΏβˆ’1 {𝑓(𝑠)}

1
πΏπ‘’π‘’π‘”π‘œ πΏβˆ’1 {𝑓(𝑠)} = βˆ’ πΏβˆ’1 {𝑓 β€² (𝑠)} π‘’π‘›π‘‘π‘œπ‘›π‘π‘’π‘ 
𝑑
𝑠+2 1 π’†βˆ’π’• βˆ’ π’†βˆ’πŸπ’•
πΏβˆ’1 {𝑙𝑛 ( )} = πΏβˆ’1 {ln(𝑠 + 2) βˆ’ ln(𝑠 + 1)} = βˆ’ (𝑒 βˆ’2𝑑 βˆ’ 𝑒 βˆ’π‘‘ ) =
𝑠+1 𝑑 𝒕

Integral
∞
𝐹(𝑑)
π‘»π’†π’π’“π’†π’Žπ’‚. βˆ’π‘†π‘– πΏβˆ’1 {𝑓(𝑠)} = 𝐹(𝑑) π‘’π‘›π‘‘π‘œπ‘›π‘π‘’π‘  πΏβˆ’1 {∫ 𝑓(𝑒)𝑑𝑒 } =
𝑠 𝑑

π‘«π’†π’Žπ’π’”π’•π’“π’‚π’„π’Šπ’π’
∞
𝐹(𝑑)
π‘π‘œπ‘šπ‘œ 𝐿{𝐹(𝑑)} = 𝑓(𝑠) οƒž 𝐿 ( ) = ∫ 𝑓(𝑒)𝑑𝑒
𝑑 𝑠
∞
𝐹(𝑑)
𝑑𝑒 π‘‘π‘œπ‘‘π‘›π‘’ π‘Žπ‘™ π‘‘π‘œπ‘šπ‘Žπ‘Ÿ π‘™π‘Ž π‘‘π‘Ÿπ‘Žπ‘›π‘ π‘“π‘œπ‘Ÿπ‘šπ‘Žπ‘‘π‘Ž π‘–π‘›π‘£π‘’π‘Ÿπ‘ π‘Ž 𝑠𝑒 𝑑𝑖𝑒𝑛𝑒 πΏβˆ’1 {∫ 𝑓(𝑒)𝑑𝑒} =
𝑠 𝑑

EJEMPLO
∞
𝑑𝑠
𝑯𝒂𝒍𝒍𝒂𝒓 π‘³βˆ’πŸ {∫ }
𝑠 𝑠2 + π‘Ž2
∞ ∞
𝐹(𝑑) 𝐹(𝑑)
𝑆𝑖 𝐿{𝐹(𝑑)} = 𝑓(𝑠) οƒž πΏβˆ’1 { } = ∫ 𝑓(𝑠)𝑑𝑠 𝑑𝑒 π‘‘π‘œπ‘›π‘‘π‘’ πΏβˆ’1 {∫ 𝑓(𝑠)𝑑𝑠} =
𝑑 𝑠 𝑠 𝑑
∞
𝐹(𝑑)
πΏπ‘’π‘’π‘”π‘œ 𝐿 βˆ’1 {𝑓(𝑠)}
= 𝐹(𝑑) οƒž 𝐿 βˆ’1
{∫ 𝑓(𝑠)𝑑𝑠} = π‘Žπ‘π‘™π‘–π‘π‘Žπ‘›π‘‘π‘œ π‘’π‘ π‘‘π‘œ π‘‘π‘’π‘›π‘’π‘šπ‘œπ‘ 
𝑠 𝑑
∞
1 𝑠𝑒𝑛(π‘Žπ‘‘) 𝑑𝑠 𝑠𝑒𝑛(π‘Žπ‘‘)
πΏβˆ’1 { 2 2 } = οƒž π‘³βˆ’πŸ
{∫ 2 2 }=
𝑠 +π‘Ž π‘Ž 𝑠 𝑠 +π‘Ž π‘Žπ‘‘